Thematic Development in Students’ Argumentative Essay - Eka Dyah Puspita Sari; Mia Fitria Agustina (Institut Agama Islam Negeri Palopo, 2022)
In writing argumentative essay, the writer should mind complete parts of the essay and other linguistic elements. The two important linguistic elements are theme and rheme. Since theme and rheme are crucial in clause structure, thematic development is regarded important in the development of text. There are three patterns of thematic development proposed by Eggins, i.e., theme reiteration, zig-zag pattern, and multiple-theme pattern. This research states its objective as to analyze the thematic development occurred in students’ argumentative essay. The occurrence of thematic development is analyzed and elaborated into the finding and discussion. This research is a qualitative research. There are 13 essays written by students. The essays are chosen randomly to maintain the objectiveness of the analysis. Those essays consist of 323 clauses. They are analyzed based on the concept of thematic development proposed by Eggins. The analysis of thematic development of the clauses shows that theme reiteration emerges as the most preferable thematic development pattern. It can be seen that 217 clauses (67,2%) in students’ essay are in forms of theme reiteration. 84 clauses (26,0%) of the essay apply zig-zag pattern in thematic development. Multiple-theme pattern comes as the least preferred thematic development pattern. It only comes up in 22 clauses (6,8%) out of 323 clauses. It can be concluded that students understand the way to develop their essays by implementing combination of thematic development. It marks a successful phase of students’ writing skill. Nevertheless, students need writing practice intensively to make their writing skill grow better.